Impact of metakaolin to partially replace granulated blast furnace slag on the performance of alkali-activated slag grouting materials and evaluation of grouting effectiveness - Bo Han; Lingjian Cai; Fengxia Chi; Wei Zhan (Materials Research Express)
In recent years, alkali-activated slag materials have garnered widespread attention in the construction field due to their environmental friendliness and excellent mechanical strength. However, optimizing their composition to reduce autogenous shrinkage remains a pressing issue. This study aims to explore the effects of partially replacing granulated blast furnace slag with metakaolin on the performance of alkali-activated slag grouting materials and evaluate its grouting effectiveness. By setting different replacement levels of metakaolin for granulated blast furnace slag, the study systematically investigates the fluidity, autogenous shrinkage, and mechanical properties of alkali-activated slag grouting materials. The experimental results show that as the amount of metakaolin increases, the fluidity of the grouting material significantly decreases, while the autogenous shrinkage rate reduces; however, the mechanical properties exhibit a complex variation trend. Specifically, when the metakaolin content is at 10%, the comprehensive performance is optimal with excellent grouting effect. This finding provides new insights and methods for optimizing alkali-activated slag grouting materials.